Implementation of Smart Library Using Radio Frequency Identification (RFID) Technology in Libraries - Arfan, Usman (Riwayat: Educational Journal of History and Humanities, 2024)
A library is a collection of information, resources, books, and services, and the structure in which it resides. To improve the quality of service and the efficiency of operation of new technologies is always of interest to librarians. Libraries are at the forefront of successfully implementing RFID technology, reducing the time and staff required for book circulation and simultaneously increasing hourly book transactions. RFID is a new generation technology of Automatic Identification and Data collection that helps to automate library processes and allows the identification of a large number of marked objects such as books, using wave radios. The proposed system is based on RFID readers, supported with antennas in the gate and transaction section, and library cards containing RFID transponders capable of storing information electronically that can be read/written even without physical contact with the help of radio media.